대학 및 실업 럭비선수들의 포지션에 따른 최대근력, 등속성 무릎과 허리 근기능 및 무산소성파워 비교 연구 - 조영현; Yeong-hyun Cho; 박지희; Ji-hee Park; 김지은; Ji-eun Kim; 유주인; Joo-in Yu; 김영표; Young-pyo Kim; 서태범; Tae-beom Seo (Ch'eyuk kwahak yŏn'gu, 2019)
[목적] 본 연구는 대학과 실업팀 럭비선수들의 포지션에 따른 최대근력, 등속성 무릎과 허리 근기능 및 무산소성파워를 비교하는 것이다. [방법] 총 54명의 럭비선수로 대학 럭비선수 포워드 그룹(FCRP, n =10), 대학 럭비선수 백스 그룹(BCRP, n =16), 실업팀 럭비선수 포워드 그룹(FPRP, n =16), 실업팀 럭비선수 백스 그룹(BPRP, n =12)으로 구분하였다. 체력관련요인으로 스쿼트, 벤치프레스, 양쪽악력으로 구성하였으며, 무릎 및 허리 등속성 근기능 검사는 Humac Norm 장비를 사용하여 측정하였다. 무산소성 페달링 파워는 Wingate로 측정 및 분석하였다. [결과] 스쿼트의 절대값과 상대적 값과 양쪽 악력은 통계적으로 유의한 차이가 없었지만, 벤치 프레스는 다른 그룹에 비해 FPRP와 BPRP에서 유의미하게 높았다. 등속성 무릎과 허리 신전과 굴곡에서는 FCRP와 BCRP에 비해 FPRP와 BPRP에서 높았고, 사후검사 결과 BPRP에서 가장 높게 나타났다. 무산소성 페달링 파워 또한 BPRP에서 가장 높았다. [결론] 본 연구 결과는 대학 럭비팀선수들과 프로팀의 포워드 선수들은 최대근력, 등속성 근기능 및 무산소성 파워 향상을 위한 체계적이고, 과학적인 훈련 프로그램이 제공되어야 한다는 정보를 제시한다. [Purpose] The purpose of this study is to compare the maximal strength, isokinetic muscle function and anaerobic capacity according to the position of college and professional rugby players. [Methods] Subjects for this study were 54 athletes and randomly divided into 4 groups: the forwards group in college rugby players (FCRP, n = 10), backs group in college rugby players (BCRP, n = 16), forwards group in professional rugby players (FPRP, n = 16), and backs group in professional rugby players (BPRP, n = 12). Physical fitness was consisted of squat, bench press, bilateral grip strength. Isokinetic knee and trunk muscle functions were measured by Humac Norm device, and anaerobic pedaling power was analyzed by Wingate test. Significant differences between groups were determined with one-way repeated ANOVA. [Results] As the result of this study, there was no statistically significant difference between the absolute and relative values of the squat and bilateral grip strengths, but bench press was significantly higher in FPRP and BPRP compared to other groups. Isokinetic knee and trunk extensor and flexor muscle strength showed stronger in FPRP and BPRP than those in FCRP and BCRP. In addition, the anaerobic pedaling power was also the highest in FPRP and BPRP. [Conclusions] Our findings suggest important information that the college rugby players and forwards in professional rugby team should be given scientific training to improve their maximum strength, isokinetic strength and anaerobic power.